Production of Truncated Recombinant Dengue Virus Envelope Protein and its Immunogenicity in BALB/c Mice - Pipattanaboon, Chonlatip; Natsrita, Piyathida; Boonha, Khwanchit; Benjathummarak, Surachet; Pitaksajjakul, Pannamthip; Ramasoota, Pongrama (Srinagarind Medical Journal, 2021)
Background and objective: Dengue is a major public health problem in tropical and subtropical countries. The four dengue virus serotypes can cause a wide range of mild to severe diseases. Many research and development efforts are ongoing to find a better effective and accessible version of vaccine, therapeutic agent, or diagnostic tool. Envelope (E) protein is a primary target for serologic diagnosis and immunization. This work aimed to express and characterize truncated E (rE74-118) protein of dengue virus serotype 2 (DENV-2) in both in vitro and in vivo properties. Methods and results: A truncated DENV-2 envelope E protein, amino acid sequence 74-118, encoding gene was amplified and cloned into the pET-32b plasmid. The recombinant plasmid was then expressed in Escherichia coli (SHuffle) to produce the recombinant protein rE74-118. Recombinant E protein in truncated form (rE74-118) was successfully constructed, expressed, and purified in the concentration of 5.8 mg/ml. The rE74-118 protein was tested for its specificity with an anti-E monoclonal antibodies and dengue patient sera. Furthermore, its immunogenicity in BALB/c mice was also tested. The results showed that the rE74-118 protein can specifically react to anti-E monoclonal antibodies and dengue patient sera. This protein also induces the humoral response with a low-level of neutralizing activity against DENV-2, as well as the protein do not show enhancing activities against all four serotypes. Conclusion: The truncated rE74-118 protein showed both antigenic and immunogenic properties in these in vitro and in vivo characterizations.